Impact of Individual Spirituality and Workplace Spirituality on Organization Commitment - Alsalemi, Jamil Abdulkarim (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aims to identify the Impact of Individual Spirituality and Workplace Spirituality on the Organization Commitment in the hospitals of the Ministry of Health in Jeddah city. It followed quantitative research methods using survey in the form of a questionnaire which was distributed electronically, the number of participants reached (181) employees at the hospitals of the Ministry of Health in Jeddah city. The research has founded results: that there is a moderate level of gratitude of workplace spirituality; and of Individual Spirituality. The results also show that there is a moderate level of Organizational Commitment, and that there is a significant Impact of Individual Spirituality on Organization engagement among workers at the hospitals of the Ministry of Health in Jeddah city. Depending on the results, the research concluded to recommendations, employees should be more aware of their colleagues at work and the nature of their work, and the hospitals of the Ministry of Health in Jeddah should be more spiritual in relations with their employees.